New Trends in Software Methodologies, Tools and Techniques - Fujita, Hamido (IOS Press, 2013)
Software is the essential enabler for the new economy and science. It creates new markets and new directions for a more reliable, flexible, and robust society. It empowers the exploration of our world in ever more depth. However, software often falls short of our expectations. Current software methodologies, tools, and techniques remain expensive and not yet reliable enough for a highly changeable and evolutionary market. Many approaches have been proven only as case-by-case oriented methods. This book, as part of SOMET series, contributes on new trends and theories in the direction in which we believe software science and engineering may develop to transform the role of software and science integration in tomorrow’s global information society.